Student's works Arctix studio semester 02: 02. Escapism / Afiqah Ahmad and Mohd. Iqbal Hashim - Ahmad, Afiqah; Hashim, Mohd. Iqbal (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The project implemented throughout history, thought movements in art and architecture which have often sought escapism, breaking away from prevailing styles. Uncovering how this impulse influenced masterworks is crucial to understanding the evolution of art and architecture.. The objective of the brief is to extract the basic design theory based on the selected masterworks. The second project aims to introduce students to explore and applies the basic design theories through films in design works. The tasks introduced the students to develop a kinetic sculpture representing moving pictures. The third project aims students to foster divergent thinking in formulating design by implementing the design theory into design scheme of a moodbox. The final project aims to introduce student expressing movement and transition of the mood accordance to the scene of the chosen movie into a mid-air portal sculture.